Immune Checkpoint Inhibitor-Based Systemic Therapy Shows Remarkable Curative Effect in a Hepatocellular Carcinoma Patient With Intractable Postoperative Recurrence and Metastases: A Case Report and Literature Review - He, Xing; Peng, Yaorong; Zhou, Zhenyu; Li, Wenbin (Frontiers in Oncology, 2022)
Abstract：  Hepatocellular carcinoma (HCC) is a systemic disease, and most patients make the diagnosis at an advanced stage. In the past, treatments for recurrence of liver cancer with multiple metastases after surgery was very palliative， The case we present is a primary massive HCC patient with inferior vena cava tumor thrombus. Radical hepatectomy was performed in July 2016. Postoperative follow-up showed that sorafenib (a tyrosine kinase inhibitor TKI , 0.8g qd) failed to stop the progression of the disease. Fourteen months later, the patient gradually developed residual liver recurrence, multiple lung metastases and suspected splenic metastasis. The monotherapy regimen was changed from sorafenib to regorafenib（a TKI,160mg qd）, but the disease continued to progress. The systematic treatment regimen was changed to Lenvatinib(a TKI，8mg qd) plus Pembrolizumab(a immune checkpoint inhibitor ICI，200mg q3w) in April 2019. Following treatment, partial remission（PR） was achieved. According to the mRECIST standard, the PFS has reached 24 months until March 2021, and the overall postoperative survival is 60 months until July 2021. The case we provide show that immune checkpoint inhibitor (ICI)-based systemic therapy may be an effective rescue treatment choice for HCC patients with intractable postoperative recurrence and metastasis.